Metabolic remodeling and immune evasion in glioblastoma: a focus on serine and lipid networks - Jiang, Dongxin; Wang, Chuheng; Zhao, Yao; Li, Yunqian (Frontiers in Oncology, 2026)
Glioblastoma (GBM) is a highly aggressive brain tumor characterized by metabolic plasticity that fuels growth, therapy resistance, and immune evasion. Among its reprogrammed pathways, serine and lipid metabolism play central roles. The serine synthesis pathway (SSP)—via PHGDH, PSAT1, and SHMT2—supports nucleotide biosynthesis, redox balance, and epigenetic regulation, especially under hypoxic and nutrient-deprived conditions. Meanwhile, fatty acid flux, FABP7-mediated PUFA transport, and cholesterol uptake reshape the tumor microenvironment, sustain glioma stemness, and promote immune suppression. Key lipid enzymes and ferroptosis regulators such as MAGL, ACSL4, and xCT modulate tumor survival and therapy response. GBM cells also exhibit high reliance on exogenous cholesterol, with dysregulation of LXR–SREBP pathways and mevalonate flux contributing to autophagy and proliferation. Therapeutic strategies targeting metabolic vulnerabilities—including SSP blockade, cholesterol homeostasis disruption, and ferroptosis induction—show synergistic effects with conventional agents like temozolomide. This review highlights the intertwined metabolic circuits in GBM and explores their translational potential as targets for precision therapy.